Analisis Keterampilan Proses Sains Tentang Usaha dan Energi Peserta Didik Kelas X SMA Negeri 8 Pontianak - Risti Wulandari; Haratua Tiur Maria; Syukran Mursid (Journal on Education, 2023)
This study aims to identify the profile of students' science process skills in answering questions about effort and energy at Senior High School 8 in Pontianak. The research employs a descriptive correlational survey method without a comparative group. The sampling technique used in this study was random sampling, involving a sample size of 65 students. The analysis of students' science process skills yielded a score of 64.48%, falling within the "sufficient" category. There is a positive relationship between science process skills and student learning outcomes (r count 0.604 > r table 0.2404), and the Sig. (2-tailed) value of 0.000 < 0.05 indicates a significant relationship between science process skills and student learning outcomes. The contribution of science process skills to student learning outcomes is 36.48%. The results of this research are expected to contribute to the development of physics teaching strategies aimed at enhancing science process skills and student learning outcomes.